Functional Traits Mediate the Natural Enemy Response to Land Use at the Local Scale - Szudruk Pascual, María Noel; Chillo, María Verónica; Garibaldi, Lucas Alejandro; Amoroso, Mariano M. (MDPI, 2023)
Arthropods are key nodes for the provision of ecosystem services such as pest control, but their response to land-use change is highly variable depending on the scale of analysis and the natural enemies’ life histories. We evaluate the effects of landscape- and local-scale variables of natural enemies’ communities on small-scale agriculture. We consider functional response traits to attain a mechanistic understanding of the effect of land-use changes on the biodiversity and resilience of natural enemies’ communities. Predator and parasitoid arthropods were collected from thirteen raspberry farms to estimate functional diversity, complementarity, and redundancy indices. We found no effects of landscape heterogeneity, local habitat, or management practices on natural enemies’ functional diversity. Regarding resilience, complementarity was high at most of the sites and was not affected by the landscape or local variables. However, redundancy was affected by two management practices. Weed control decreased natural enemies’ abundance as well as the abundance of walker generalist predators and flying specialist parasitoids, while habitat richness decreased flying generalist predators. These results highlight the importance of management when the landscape matrix is heterogeneous. We conclude that small-scale agriculture in a heterogeneous landscape supports a functionally diverse enemy community, potentially promoting the resilience of pest control to land-use change.